Photophysical properties of new p-phenylene- and benzodithiophene-based fluorophores for luminescent solar concentrators (LSCs). (July 2020) - Albano, Gianluigi; Colli, Tony; Biver, Tarita; Aronica, Laura Antonella; Pucci, Andrea
Abstract: In this study, we report on the synthesis of new organic fluorophores containing either the p -phenylene or the benzodithiophene cyclic nucleus connected to thiophene units via triple bonds and carbonyl group, and on their application for the fabrication of luminescent solar concentrators (LSCs). Their optical properties were evaluated. Independent of the core, dyes containing the CO-thiophene residues seem to be the most promising for LSCs applications. In fact, carbonyl groups slightly enhance the quantum yield but significantly increase the red-shift of the emission so that the superimposition between the absorbance spectrum and the emission one is diminished. In the case of the benzodithiophene centre, light emission in the yellow-red portion of the spectrum is achieved. The latter dye is then selected for tests in a poly(methyl methacrylate) (PMMA) matrix. It showed good compatibility and homogenous distribution, no auto-absorption phenomena, and optical efficiencies of about 8% at 1 wt. %, i.e. comparable with those PMMA/Lumogen Red films in the same range of concentration. Graphical abstract: Image 1 Highlights: New p -phenylene or benzodithiophene based fluorophores were easily obtained. Photophysical properties of all fluorophores in solution were investigated. Carbonyl groups favored significant bathochromic effects and high Stokes shifts. Important solvatochromism was observed for the p -phenylene-based fluorophore. PMMA films doped with the benzodithiophene derivative showed promising performances as solar collector.